Scarlet Experiment : Birds and Humans in America - Karnicky, Jeffrey (Book collections on Project MUSE., 2016)
"Scarlet Experiment explores how humanity's relationship with birds has been influenced by governmental agencies, literary renderings, and the conservation movement and uses six bird species to study the management of bird life in America from the nineteenth century to the present"--